Association between Serum Vitamin C and the Blood Pressure: A Systematic Review and Meta-Analysis of Observational Studies - Li Ran; Wenli Zhao; Xiaodong Tan; Hongwu Wang; Kaito Mizuno; Ken Takagi; Ye Zhao; Huaien Bu (Hindawi-Wiley, 2020)
Background. Hypertension is regarded as a major and independent risk factor of cardiovascular diseases, and numerous studies observed an inverse correlation between vitamin C intake and blood pressure. Aim. Our aim is to investigate the relationship between serum vitamin C and blood pressure, including the concentration differences and the correlation strength. Method. Two independent researchers searched and screened articles from the National Library of Medicine, Cochrane Library, Web of Science, China National Knowledge Infrastructure, VIP databases, and WANFANG databases. A total of 18 eligible studies were analyzed in the Reviewer Manager 5.3 software, including 14 English articles and 4 Chinese articles. Results. In the evaluation of serum vitamin C levels, the concentration in hypertensive subjects is 15.13 μmol/L lower than the normotensive ones (mean difference=−15.13, 95% CI [-24.19, -6.06], and P=0.001). Serum vitamin C has a significant inverse relation with both systolic blood pressure (Fisher's Z=−0.17, 95% CI [-0.20, -0.15], P<0.00001) and diastolic blood pressure (Fisher's Z=−0.15, 95% CI [-0.20, -0.10], P<0.00001). Conclusions. People with hypertension have a relatively low serum vitamin C, and vitamin C is inversely associated with both systolic blood pressure and diastolic blood pressure.